Understanding Occupational & Organizational Psychology - Lynne J Millward (USA Sage Publications, 2005)
Understanding Occupational and Organizational Psychology provides full coverage of the British Psychological Society's training requirements for becoming a chartered occupational psychologist and complies with European training guidelines for industrial, work, and organizational psychology. This book will prompt and inspire further reading and research as well as ideas for dissertations, problem formulation and the creative application of knowledge to various situations.
Keywords: Organizational psychology; Psychology; Textbooks; Business Psychology (HRM1089-N)